2009
DOI: 10.1007/s12028-009-9202-3
|View full text |Cite
|
Sign up to set email alerts
|

Intra-arterial Air Thrombogenesis after Cerebral Air Embolism Complicating Lower Extremity Sclerotherapy

Abstract: We provide radiological evidence of hyperbaric oxygen therapy resolving intraarterial air but also demonstrate the thrombogenic potential of this procedural complication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…106 Secondary thrombosis following bubble exposure was reported in one PSS patient where thrombi were observed in the affected artery following the dissolution of the gas emboli. 7 Bubbles can also cause a progressive decline in cerebral blood flow even if they do not completely occlude vessels. 117,121 The nomenclature referring to the observed bubbles has been varied and often less than accurate.…”
Section: Paradoxical Gas Embolismmentioning
confidence: 99%
“…106 Secondary thrombosis following bubble exposure was reported in one PSS patient where thrombi were observed in the affected artery following the dissolution of the gas emboli. 7 Bubbles can also cause a progressive decline in cerebral blood flow even if they do not completely occlude vessels. 117,121 The nomenclature referring to the observed bubbles has been varied and often less than accurate.…”
Section: Paradoxical Gas Embolismmentioning
confidence: 99%
“…The etiology of these isolated events remains to be determined and further studies are required. [18][19][20][21] However, the fact that visual disturbances have been reported following liquid sclerotherapy suggests that mechanisms unrelated to bubbles, such as vasospasm from the sclerosant itself or secondary to vasoactive moieties released from venous endothelium as it is destroyed, may be involved.…”
mentioning
confidence: 99%
“…26 Other proposed mechanisms include the fact that symptoms occur as a result of air embolus, and confirmatory MRI images of air bubbles in the cerebral circulation of symptomatic patients suffering CVA have been reported. 12,13 Similar neurological symptoms have also been observed in divers after surfacing, whereby air bubbles have been shown to cause transient neurological symptoms. 27 It has also been suggested that an inflammatory reaction to the sclerosant may cause vasospasm resulting in symptoms.…”
Section: Discussionmentioning
confidence: 63%
“…The timing of the onset of symptoms was highly variable. In eight cases, symptoms occurred within minutes of treatment, 7,8,12,13,16,17 in three cases this occurred at 1 to 4 hours, 14,15,18 two cases reported symptoms the following day within 24 hours, 11,13 and the remaining cases were at 2 days, 3 days, and 5 days following treatments. 9,10,13 In two cases, residual weakness was observed at the time of discharge from hospital, and there was one reported fatality in the case of the patient who suffered a hemorrhagic stroke.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation